PENGUNGKAPAN TANGGUNG JAWAB PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA MASA PANDEMI COVID-19 - Nurlaila Nurlaila; Nurwani Nurwani (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2023)
COVID-19 has brought human activities to a halt which has an impact on business continuity, most companies have stopped their operational activities, making companies experience losses. This study aims to examine the effect of CSED and profitability on the company value of pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2015-2019 and the period 2020 to determine the impact of COVID-19. The population of this study was 10 pharmaceutical companies, purposeful sampling technique was applied to select seven companies as samples. Data is obtained from reports of information or material facts about the impact of the COVID-19 pandemic on pharmaceutical companies from www.idx.co.id website. The results showed that CSED had a positive and significant effect on company value, while profitability had a positive but not significant effect on company value.